Double-balloon endoscopy WAS effective in diagnosing small intestinal duplication: a case report - Nadatani, Yuji (Springerplus, 2016)
INTRODUCTION: Ileal duplications are encountered infrequently in adults, because symptoms including abdominal pain, intussusception, hemorrhage, and perforation usually present in early childhood. In this report, we present an adult case of ileal duplication that was revealed by double-balloon endoscopy (DBE). CASE DESCRIPTION: A 73-year-old Japanese man presented with anemia and melena. Anal DBE detected the narrow opening of an extra lumen in the ileum about 100 cm proximal to the ileocecal valve. Enteroclysis via DBE showed a 5-cm-long ileal diverticulum-like structure at the mesenteric side of the ileum. No ectopic gastric mucosa was detected by technetium-99m pertechnetate scintigraphy. The final diagnosis was ileal duplication. DISCUSSION AND EVALUATION: This is the first report of tubular ileal duplication diagnosed by using DBE. The small intestinal duplication opening was not detected by using VCE and plane CT in this case, but was found by using DBE. CONCLUSIONS: The present case demonstrates that DBE was useful in the diagnosis of an adult small intestinal duplication that was not visualized by other modalities.